2022
DOI: 10.3390/children9030384
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Behavioral Aspects of Adolescent Endometriosis: A Review of the Literature

Abstract: The majority of young women will experience discomfort associated with menstrual cycles and miss out on education and social opportunities. Endometriosis, the presence of endometrial glands and stroma outside of uterus, is the most common cause of secondary dysmenorrhea and characterized by pain despite treatment with nonsteroidal anti-inflammatory drugs and hormonal agents. The true prevalence of adolescent endometriosis is not clear. Delay in diagnosis leads to persistent pain, affects quality of life, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 83 publications
(120 reference statements)
1
4
0
Order By: Relevance
“…The results of conducted multivariate analysis linked CRP levels to the VAS score and estradiol levels to the McGill pain index. Our data fit into the conception that estrogen-induced neuro-immune interaction plays a key role in peripheral sensitization while enhancing EMS-associated neuropathic pains [ 24 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of conducted multivariate analysis linked CRP levels to the VAS score and estradiol levels to the McGill pain index. Our data fit into the conception that estrogen-induced neuro-immune interaction plays a key role in peripheral sensitization while enhancing EMS-associated neuropathic pains [ 24 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 83%
“…Estradiol is known to directly stimulate prostaglandin E2 synthesis, thereby enhancing noxious stimuli in a COX2-dependent manner [ 23 ]. Many studies associate EMS with increased levels of IL-1β, IL-6, IL-8, TNF-α, CCL-2, CCL-5, and VEGF in systemic circulation and peritoneal fluid [ 3 , 24 , 25 , 26 ]. Due to the central role of pro-inflammatory cytokines in the clinical picture of the disease, non-steroidal anti-inflammatory drugs (NSAIDs) remain first-line painkillers in their management.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some prenatal factors may also be associated with the onset of DIE in adolescence, such as preeclampsia and low birth weight [21]. The underlying mechanism would be the fetal hypoxic environment caused by placental insufficiency that would increase endometrial sensitivity to progesterone [23] and the altered platelet activation leading to augmented angiogenesis [13]. It is hypothesized that the presence of a fetal hormonal milieu then facilitates the development of DIE [24].…”
Section: Pathogenesis Of Die In Adolescentsmentioning
confidence: 99%
“…Endometriosis causes dysmenorrhea, chronic pelvic pain, dyspareunia, painful defecation, and infertility [1]. Its epidemiology is still controversial; however, it has been reported that 10-15% of women of reproductive age suffer from endometriosis [2][3][4][5]. Endometriosis-related pain is severe in many cases and causes school absenteeism among adolescents and has a severe impact on work productivity [6,7].…”
Section: Introductionmentioning
confidence: 99%